2020
DOI: 10.1097/sap.0000000000002443
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Surgery and the COVID-19 Pandemic

Abstract: Background: A novel coronavirus disease (COVID-19) was first reported in December 2019 in China and was soon declared a pandemic by World Health Organization. Many elective and nonessential surgeries were postponed worldwide in an effort to minimize spread of disease as well as to conserve resources. Our goal with this article is to review current practice guidelines in setting of the COVID-19 pandemic, based on available data and literature. Methods: Websites pertaining to surgical and medical societies, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 47 publications
0
51
0
5
Order By: Relevance
“…Several other articles have been published on the necessary reorganization of surgical departments during the COVID-19 pandemic and the decline in surgical activity resulting from the medical measures implemented in response to this pandemic 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 . However, none of them has precisely evaluated the decline in trauma cases, and especially in maxillofacial trauma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several other articles have been published on the necessary reorganization of surgical departments during the COVID-19 pandemic and the decline in surgical activity resulting from the medical measures implemented in response to this pandemic 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 . However, none of them has precisely evaluated the decline in trauma cases, and especially in maxillofacial trauma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the study has demonstrated that the risk of COVID-19 is low following cancer surgery, it is important to highlight the need for a thorough, individualised multi-disciplinary decision on the timing of surgery. [ 16 ] The risks and benefits of each procedure should be carefully weighed against the potential further spread of COVID-19 and the need to utilise our resources in the most effective manner [ 25 ]. This will require flexibility at a regional level, given each centre’s available resources and the current prevalence of COVID-19 in the local area [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plastic surgeons must be apprised of the most current state and society guidelines on the status of elective procedures and be amenable to adapt in the event of a second COVID-19 surge. 6 …”
Section: Introductionmentioning
confidence: 99%